The effect of organizational culture on material risk among Malaysian construction industries - Nur Syafiqah, Abdul Malik; Adeleke, A. Q. (Penerbit Akademia Baru, 2018)
This paper assessed the significant relationship between organizational culture and material risk among Kuantan Malaysian construction industries. Survey was conducted among 10 registered G7 contractors operating in Kuantan construction industry. Proportionate stratified random sampling was used out of which 10 questionnaires were distributed for pilot study. Methodologically, this research is perhaps the first to assess the relationship between organizational culture and material risk among Malaysian construction industries with five point Likert scale categories of material risk from previous studies. Statistical analysis affirmed a significant positive relationship between organizational culture and material risk among Malaysian construction industries through Statistical Package for Social Sciences (SPSS).